2011
DOI: 10.1007/s12010-011-9288-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biosensors for Organophosphate Pesticides

Abstract: Organophosphates, amongst the most toxic substance known, are used widely in agriculture around the world. Their extensive use, however, has resulted in their occurrence in the water and food supply threatening humans and animals. Therefore, there is a need for determination of these neurotoxic compounds sensitively, selectively, and rapidly in the field. The present work is a brief review on the recent advancements in amperometric, potentiometric, and optical biosensors using genetically engineered microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Organophosphorus compounds (OP) are neurotoxic chemicals that can be used as nerve agents (e.g., Sarin) or agricultural pesticides (e.g., parathion). , OP compounds present high toxicity to human health by inactivating acetylcholinesterase that is essential for proper functioning of nerve cells; therefore, it becomes important for us to detect even trace amounts of OP present as a chemical warfare agent or as an environmental contaminant. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Organophosphorus compounds (OP) are neurotoxic chemicals that can be used as nerve agents (e.g., Sarin) or agricultural pesticides (e.g., parathion). , OP compounds present high toxicity to human health by inactivating acetylcholinesterase that is essential for proper functioning of nerve cells; therefore, it becomes important for us to detect even trace amounts of OP present as a chemical warfare agent or as an environmental contaminant. …”
mentioning
confidence: 99%
“…Trace amount of OP can be detected using traditional analytical methods such as gas and liquid chromatography, which are nonportable and therefore unsuitable for on-site detection. As such, biosensors that offer portability as well as good specificity and sensitivity become attractive alternative methods for OP detection. ,, Among the various kinds of biosensors available, whole-cell biosensors are favorable due to their relatively low cost of sustainable production and operational stability. Whole-cell biosensors are usually designed to consist of sensing and reporter modules.…”
mentioning
confidence: 99%
“…In this study, we have shown that engineered microbial combinations can both degrade and detect toxic OPs with incomparable specificity and sensitivity using electrochemical readout. 1,33,40,[45][46][47][48][49][50][51][52][53]65 E. coli were engineered to express OPH on the cell surface to degrade organophosphate pesticides to p-NP, even following E. coli lyophilization. We also engineered electroactive microbes, S. oneidensis, to express a critical EET protein, CymA, in the presence of p-NP.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Pesticides block the catalytic activity of the active center, thus acting as inhibitors of AChE. This results in the accumulation of acetylcholine in the synaptic membrane, which blocks the nerves to process the signals properly [16].…”
Section: Principle Of Btamentioning
confidence: 99%